Psychosomatisch-psychotherapeutische Unterstützung von Covid-19-Patient:innen in häuslicher Quarantäne: eine Inhaltsanalyse supportiver Telefongespräche - Dinger, Ulrike; Morschek, Lorena; Stangl, Laura; Israel, Dominik; Schopper, Alexander; Thanbichler, Eric; Zumbaum-Fischer, Franziska; Wenz, Theresa; Merle, Uta; Tarbet, Karin; Nikendei, Christoph (Zeitschrift für psychosomatische Medizin und Psychotherapie, 2022)
Objectives: During their domestic quarantine, Covid-19 patients face major physical, psychological and social challenges. The description of support needs and specific topics brought to supportive conversations will be used to add to the body of knowledge about stressors and resources. Methods: A total of 109 telephone conversations with 69 quarantined Corona patients were documented by psychotherapists and physicians at Heidelberg University Hospital from November 2020 to April 2021. Subsequently, clinical documentations were analyzed according to a qualitative content analysis. Results: Most physical complamints related to cardio-respiratory symptoms (29 %), previous illnesses (24 %), and exhaustion or fatigue (16 %). On the psychological level, patients reported mainly anxiety (31 %) and depressive symptoms (16 %). On a social level, patients described stress related to family (56 %), work (20 %), and time in quarantine (16 %). Social support, individual coping strategies, a positive prognosis on the course of the corona disease, psychotherapy, and satisfactory medical care were mentioned as relieving factors. Therapeutic interventions aimed at stabilization and consisted of psychoeducation, relaxation techniques, and general counseling. Conclusions: The study shows that physical complaints, psychological symptoms, and social factors are brought into telephone support conversations. The support offer met a high demand and was well accepted.